The first twenty years. - Scottish National Gallery of Modern Art, Edinburgh; International Festival Edinburgh 1980 (Edinburgh : National Galleries of Scotland, 1980)
Rosso, Medardo ; Klee, Paul ; Lewis, Wyndham ; Jawlensky, Alexei ; Matisse, Henri ; Giacometti, Alberto ; Kirchner, E.L. ; Ernst, Max ; Lichtenstein, Roy ; Hanson, Duane ; Kitaj, R.B. ; etc.
Twenty Modern Masterpieces : Acquered during the first twenty years of the Gallery, Scottish National Gallery of Modern Art 1960 to 1980, exhibition 20/80 held at the time of the Edinburgh International Festival, 1980
boek